2018
DOI: 10.11604/pamj.2018.29.217.15366
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of snake bites in selected areas of Kenya

Abstract: IntroductionSnake bites are a silent public health problem in Kenya. Previous studies on snake bites in the country have mainly focused on identifying offending snake species, assessing the severity of envenomation and testing the efficacy of antivenom. Factors associated with snake bites in the country are yet to be fully understood. The aim of this work was to determine pharmaco-epidemiological factors associated with snake bites in areas of Kenya where incidence, severity and species responsible for snake b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
30
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 17 publications
12
30
5
Order By: Relevance
“…Some girls and the elderly were however bitten at home or in school facilities, indicating that everyone is at risk of snakebites [7, 24, 31, 43, 51, 52]. Contrary to our findings, some studies in Africa actually report relatively higher snakebite prevalence in children, including girls, probably as a result of higher child-labour engagement or poorer parental care and supervision in such areas [23, 31, 50, 51, 53, 54, 55, 56].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Some girls and the elderly were however bitten at home or in school facilities, indicating that everyone is at risk of snakebites [7, 24, 31, 43, 51, 52]. Contrary to our findings, some studies in Africa actually report relatively higher snakebite prevalence in children, including girls, probably as a result of higher child-labour engagement or poorer parental care and supervision in such areas [23, 31, 50, 51, 53, 54, 55, 56].…”
Section: Discussioncontrasting
confidence: 99%
“…Our data from all three respondent groups indicated that farmlands and bushes, and to a lesser extent, residential areas and roads are typical habitats for snakebite, as corroborated by several other studies in rural Africa [16, 31, 38, 50, 51]. Likewise, majority of bites occur during the peak farming periods (e.g.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations